Estudo Morfométrico de Ovinos da Raça Crioula Lanada no Sul do Brasil: Um Subsídio para a Conservação In Situ - SILVA, Marcelo Corrêa da (2011)
Intense selection pressure is associated with global economy and market conjectures, which has great influence and threatens the sustainability of genetic varieties used in traditional crop and livestock production. Abrupt change of such breeds for exotic ones is decreasing genetic diversity and has extinguished many domestic varieties worldwide. The Crioula Lanada sheep breed is a Brazilian cultural, ecological and genetic patrimony which was almost extinct in the mid twentieth century. Conservation activities were established in Southern Brazil with collaboration of a farmer´s association and the foundation of an institutional flock. Currently, breed population is still small and little information about these animals is available. It is necessary that characterization studies subsidize the conservation of this important genetic resource so that farmers can make the best of its use in different production systems. A phenotypical study was undertaken to help handling activities and in situ conservation. 15 morphometric variables (cm) and body weight (kg) were evaluated in 67 male and 812 female sheep, distributed in five age categories and raised in four municipalities of Rio Grande do Sul and two of Santa Catarina, Southern Brazil. The influence of age, sex, wool type and geographic location (fixed effects) on morphometric measures was tested, in addition to correlation, factor analysis and the discrimination of the Crioula Lanada sample in Serrana or Fronteira ecotype. Variance, means test, descriptive, correlation analysis and multivariate statistics were carried out using the Statistical Analysis System Program (SAS, 2002). Age, sex and geographic location revealed significant effect (p<0,001) on morphometric measures. Different averages between age categories depend on which variable is being analyzed, being all means equivalent when considering animals older than 3 years. Most correlations where significant (p<0,05), being thoracic perimeter with body weight the strongest (0,72). Correlation between head and body measures were medium or weak, being strong between body weight. Head and body variables are more related among themselves. Leg, arm and tail measurements revealed weak correlations with body weight, besides not being different (p>0,05) among age categories. Using multivariate statistics, it was possible to explain 81% of variance with only two factors, whereat three groups of variables were identified: one with body measures, the second with head measures and the third with thoracic measures and body weight. 95% of Fronteira sheep were correctly classified in its geographic location being possible to correctly classify animals of each herd of the Serrana ecotype and the ecotypes themselves. The results found in this study can be used as a dialectic instrument to study farmers perceptions and develop an in situ conservation program for the Crioula Lanada breed